Developing Best Practice Guidance for Discharge Planning Using the RAND/UCLA Appropriateness Method - Tyler, Natasha; Planner, Claire; Byrne, Matthew; Blakeman, Thomas; Keers, Richard N.; Wright, Oliver; Pascall Jones, Paul; Giles, Sally; Keyworth, Chris; Hodkinson, Alexander; Taylor, Christopher D. J.; Armitage, Christopher J.; et al. (Frontiers in Psychiatry, 2021)
Background: Discharge from acute mental health inpatient units is often a vulnerable period for patients. Multiple professionals and agencies are involved and processes and procedures are not standardised, often resulting in communication delays and co-ordination failures. Early and appropriate discharge planning and standardisation of procedures could make inpatient care safer. Aim: To inform the development of a multi-component best practice guidance for discharge planning (including the 6 component SAFER patient flow bundle) to support safer patient transition from mental health hospitals to the community. Method: Using the RAND/UCLA Appropriateness method, a panel of 10 professional stakeholders (psychiatrists, psychiatric nurses, clinical psychologists, pharmacists, academics and policy makers) rated evidence-based statements. 668 statements corresponding to 10 potential components of discharge planning best practice were rated on a 9-point integer scale for clarity, appropriateness and feasibility (median ≥7-9) using an online questionnaire then remote online face-to-face meetings. Results: Five of the six ‘SAFER’ patient flow bundle components were appropriate and feasible for inpatient mental health. One component, ‘Early Flow’, was rated inappropriate as mental health settings require more flexibility. Overall, 285 statements were rated as appropriate and feasible. 44 statements were considered appropriate but not feasible to implement. Discussion: This consensus study has identified components of a best practice guidance/intervention for discharge planning for UK mental health settings. Although some components describe processes that already happen in everyday clinical interactions (i.e. review by a senior clinician), standardizing such processes could have important safety benefits alongside a tailored and timely approach to post-discharge care.